Eksistensi Tenun sebagai Warisan Budaya : Pengenalan dan Pelestarian untuk Generasi Muda di Jl. Pangeran Diponegoro RT 23 RW 08, Kelurahan Sebengkok, Tarakan Tengah - Nurul Hidayat; Monika Martiyoli Urei; Nur Rahmi; Eka Wulandari; Felisyashandi Felisyashandi; Andrik Radika Saptaputra; Karya Agung (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Low interest among the younger generation in local culture, particularly in traditional weaving skills, remains a significant concern in the city of Tarakan. Yet, weaving is one of Indonesia’s cultural heritages with high artistic and economic value. In response to this issue, a weaving training program was conducted at Jl. Pangeran Diponegoro RT 23 RW 08, Sebengkok Subdistrict, Central Tarakan, with the aim of fostering cultural appreciation among youth while equipping them with productive skills. The activity was held on September 13, 2025, from 13:00 to 16:00 Central Indonesian Time (WITA), at the home of a local resident in Sebengkok. The participants consisted of six male students from grade 10 of a vocational high school and four adult female participants. The methods employed in this program included cultural education, hands-on weaving practice, and documentation. This community engagement activity reflects a comprehensive approach to cultural preservation while also opening economic opportunities for the local community. The program included the introduction of weaving's cultural values, basic skill training, small-scale business mentoring based on woven products, and community development efforts..